Transceiver coexistence design of MIMO radar and MIMO communication under Gaussian model uncertainty - Xin He; Lei Huang (IET Signal Processing)
Abstract This paper proposes a transceiver coexistence design of multiple‐input multiple‐output (MIMO) radar and MIMO communication under Gaussian model uncertainty. To tackle the mutual interference and the model uncertainty problems, the transceivers of the radar system and the communication system are jointly designed to minimise the total transmit power of the radar system and the communication system, while the signal‐to‐interference‐plus‐noise‐ratios (SINRs) or effective SINR (ESINR) of the radar system and the mean square error (MSE) of the communication system are guaranteed with small outage probability. Safe approximations are proposed for the probabilistic constraints, and a converged iterative algorithm is proposed for the joint transceiver design. Owing to the MSE formulation, the convex relaxation for the communication transmitter is proved to be tight. Furthermore, the tight communication relaxation provides an effective way to check whether the radar error is majorly due to numeric error or the possible rank‐one relaxation error. Extensive simulation results show that the proposed iterative algorithm converges, the possible radar rank‐one relaxation error is trivial with respect to the numeric error, and the quality of service in terms of SINR, ESINR, MSE and bit error rate (BER) in the proposed coexistence system are robust against model uncertainty with the cost of using extra transmit power.